Evaluating Diaphragmatic Rapid Shallow Breathing Index for Predicting Weaning Outcome of Ready to Wean Mechanically Ventilated Patients: A Prospective Cohort Study in A Tertiary Care Intensive Care Unit of Bangladesh (Bangladesh Critical Care Journal, 2026)
Background: Weaning failure is a common problem in mechanically ventilated ICU patient. There are many weaning predictors to reduce weaning failure, among them Rapid shallow breathing index (RSBI) is widely used. But several studies showed various specificity and sensitivity of RSBI. Diaphragmatic dysfunction is found to be a vital cause of weaning failure. Taking Diaphragmatic dysfunction in consideration, the diaphragmatic rapid shallow breathing index(D-RSBI) is a new and promising tool to predict weaning outcome. Its accuracy in predicting weaning outcome of our mixed ICU population need to be evaluated. Procedure: This prospective cohort study was carried out at the Department of Anesthesia, Analgesia and Intensive Care Medicine, Bangladesh Medical University, Dhaka, Bangladesh for a period of 12 months. A total of 32 patients requiring mechanical ventilation for more than 48 h who were ready to perform a spontaneous breathing trail (SBT) were included in this study. At 30min of SBT, Respiratory rate, tidal volume and diaphragm displacement (DD) are measured with diaphragm ultrasonography. Then the weaning outcome was recorded. Receiver operating characteristic (ROC) curves were used to evaluate the diagnostic accuracy of D-RSBI and RSBI. Result: Among the total 32 enrolled subject, 14 (44%) were successfully liberated from mechanical ventilation. The 18 (56%) patients who failed weaning, 9 (50%) failed the SBT and reconnected to the ventilator, 5 (28%) were reintubated within 48 h of extubation and 4 (22%) required NIV support within 48 h of extubation. Receiver operating characteristic (ROC) analysis showed that DRSBI with the best diagnostic accuracy for predicting weaning failure (AUROC = 0.929; p value 0.00) with a cutoff of DRSBI >1.7 breaths/min/mm at 30 min of SBT, On other hand RSBI showed best sensitivity and specificity with a cut off value >63 breaths/min/liter (AUROC = 0.796; p value 0.005). Conclusion: Diaphragmatic rapid shallow breathing index is a good and superior weaning predictor to RSBI.Bangladesh Crit Care J March 2026; 14 (1): 4-10